Questões raciais na formação dos educadores da comunidade quilombola Mussuca : a experiência da pesquisa ação na construção do conhecimento docente - Silva, Danielle Lima (2016)
Mussuca is a quilombola village (community formed by former slaves descendants) which is located at the municipality of Laranjeiras in the Brazilian State of Sergipe. A place made of resistances and contradictions. To analyse the elements that deny or widen the professor’s knowledge about the ethnic-racial questions by taking as reference the participation of the professors in the course of extension for teachers formation at the Mussuca Quilombo, which is the central objective of this research. The central question was: Why did the acting professors have constant difficulties working the perspective of quilombola school teaching? Our hypothesis is that the cultural, economic and political factors that resist to the ethnic-racial diversity, the exclusively Eurocentric knowledge historically inserted in people’s lives who are in an educational environment, beyond the absence of formation for the educational workers on themes related to African and African-Brazilian values; this causes the denial of a school basis that respects and works the differences at the school’s institutional body. The analysis made by the study approaches the historical dialectical materialism, since its development has parted from the material reality existent at the community and its contradictions. We have used as theoretical framework the bibliographic references, scientific papers, dissertations and theses. The research’s approach is qualitative, approaching the field of research-action, is justified by the workshops that were made with the teachers from the teaching institutions of this community. We have applied as research instruments the questionnaire and observation techniques. This study’s results prove the hypotheses made here and one of them is in the results compiled during the continuous formation that is being developed by the Observatory of Teaching Project (the Federal University of Sergipe – UFS), with positive reflections in the teacher’s way of thinking about the racial question.